Environmental education essentials for project designers in Angola - Mpaxi, Lic. Mbongo; Méndez Santos, Isidro Eduardo; Carvajal Hernández , Bárbara María (Transformación, 2024)
The article provides a selection of essential contents supporting environmental education of project designers in Angola. To attain such objective knowledge; abilities and values to be pursued are listed. The selection was completed by means of a thorough inquire based on the application of analysis and synthesis, historical, logical, inductive, deductive and system methods. The need of Angolan builders of knowing the environmental impact of constructions is backed up. At the same time, the professional abilities allowing the future graduates to contribute to the preservation of environment during the stages of design, construction, exploitation and demolition of buildings is described.